2014
DOI: 10.1590/s0034-8910.2014048004793
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Control Program and patient satisfaction, Rio de Janeiro, Brazil

Abstract: OBJECTIVE To evaluate factors associated with users’ satisfaction in the Tuberculosis Control Program.METHODS A cross-sectional study of 295 patients aged ≥ 18 years, with two or more outpatient visits in the Tuberculosis Control Program, in five cities in the metropolitan region of Rio de Janeiro, RJ, Southeastern Brazil, in 2010. Considering an estimated population of 4,345 patients, the sampling plan included 15 health care units participating in the program, divided into two strata: units in Rio de Janeiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
1
11
0
7
Order By: Relevance
“…DOT was provided more to SPPT (83.3%) and MDR-TB (100%) compared to SNPT (20%) and EPT (28.2%). Similar results were found in other countries like in Brazil [15][16][17], Ethiopia [18] Indonesia [19], and India [14]. A study by Lavor et al [15], found that DOTS was partially implemented in Brazil [15].…”
Section: Discussionsupporting
confidence: 79%
“…DOT was provided more to SPPT (83.3%) and MDR-TB (100%) compared to SNPT (20%) and EPT (28.2%). Similar results were found in other countries like in Brazil [15][16][17], Ethiopia [18] Indonesia [19], and India [14]. A study by Lavor et al [15], found that DOTS was partially implemented in Brazil [15].…”
Section: Discussionsupporting
confidence: 79%
“…A demora para atendimento associada à forma de organização do serviço era vista pelos usuários como um fator de desmotivação e insatisfação 16 . Estudo no município do Rio de Janeiro mostrou que as dimensões acessibilidade/conveniência, ambiente físico e disponibilidade de recursos nas unidades de saúde com PCT foram as que geraram os menores índices de satisfação dos usuários 17 . Lima et al 18 , em estudo sobre abandono de tratamento da TB, apontam que usuários avaliaram positivamente a presteza no agendamento da primeira consulta, na solicitação de exames e dispensação de medicação, e como aspecto negativo a demora para atendimento.…”
Section: Inaugurado Em 2004 O Ambulatório Margareth Prettiunclassified
“…No que diz respeito ao nível de escolaridade, parte considerável dos indivíduos tinham nível superior (40,0%), (Tabela 1). De modo divergente, a pesquisa feita por Portela et al (2014), no estado do Rio de Janeiro, no ano de 2009, revelou que a maioria dos pacientes em tratamento para TB possuíam baixa escolaridade.…”
Section: Resultsunclassified
“…A TB é um importante problema de saúde pública, assim as dificuldades na adesão ao esquema terapêutico podem ocasionar o abandono ou descontinuidade do mesmo, o que pode acarretar maior durabilidade do tratamento, multirresistência bacteriana, além de sofrimento psíquico e social ao paciente. Portanto, é importante identificar os principais problemas enfrentados durante o TDO no intuito de que sejam elaboradas e implantadas intervenções que contribuam para adesão ao tratamento e 605 consequente declínio das taxas de morbidade e mortalidade relacionadas a essa patologia (PORTELA et al, 2014).…”
Section: Introductionunclassified